Development of pH-sensitive intranasal pregabalin gel and its pharmacokinetic evaluation - Muhammad Fathiy Mohd Mutalabisin
Intranasal drug delivery study is one of the promising methods of administration for central nervous system (CNS) drugs. It brings drugs directly to the brain through olfactory and trigeminal nerve. Any CNS drugs delivered via oral and intravenous have the potential to be delivered via nasal route. The main advantage of using intranasal route is to lessen the peripheral side effects by reducing the dose administered. Nasal route also brings its own challenge which is high mucociliary clearance rate. To solve the challenge, this study attempted an intranasal formulation using pH-sensitive polymer. Pregabalin was used as the model drug. Simple and robust analytical method for quantitation of Pregabalin has been developed and validated by using HPLC with UV detector. Validation criteria including specificity, linearity, limit of quantification (LOQ), limit of detection (LOD), precision and accuracy were met with International Conference on Harmonisation (ICH) standard. The method was linear with correlation coefficient (r2) 0.992 and limit of quantitation (LOQ) of 15 µg/ml. The method was applied to commercial Pregabalin (Pregabalin Sandoz) for assay analysis with 100.37 ±2.94 % accuracy. The formulation of pH-sensitive intranasal Pregabalin gel has been characterized by compatibility study, pHsol-gel and gelation time test, viscosity study, drug assay test, clarity test and in-vitro dissolution test. The formulation consists of 0.35%, 0.4% and 0.45% of Carbopol 940 with distilled water and Pregabalin. Compatibility study had shown no interaction within the formulation. From in-vitro dissolution test, there was no significant difference of drug release between the formulations (p>0.05) because of the slight difference in percentage of Carbopol 940 used. For bioanalytical method development, Aspirin had been used as the internal standard (IS) because it did not interact with Pregabalin and bioanalytical sample (brain and plasma). The HPLC parameters also had been optimized and suitable extraction solvent (Acetonitrile) was selected. The developed method was validated according to Bioanalytical Method Validation Guidance for Industry from United States Food and Drug Administration (US FDA) and met with the required criteria. The validated criteria included specificity, calibration curve, lower limit of quantification (LLOQ), recovery, precision and accuracy. Linearity of the method was measured by r2 with the result higher than 0.99 for both plasma and brain. LLOQ for the method was 25 and 75 µg/mL for plasma and brain respectively. The validated method had been applied for pharmacokinetic analysis in rat’s plasma and brain. Brain AUC0-4 for intranasal route was higher compared to oral route. At first sampling point (15 minutes), Pregabalin concentration in the brain of pH-sensitive intranasal Pregabalin gel (0.4% Carbopol 940) was highest compared to intranasal drop and oral solution. In conclusion, pH-sensitive intranasal Pregabalin gel has better Pregabalin delivery to the brain compared to normal intranasal drop solution and oral Pregabalin.